Consumer's appreciation of regional image and the perceived quality of rural tourism - Efthalia Dimara; Anastasia Petrou; Dimitris Skuras (European Regional Science Association (ERSA), 2002)
Tourists' perception of regional image is critical as regards the degree of satisfaction obtained from the overall tourism experience. The present paper analyses the ways in which a region's image is incorporated into the tourist products and the overall tourism experience. Regional image is acknowledged to entail elements of the socio-cultural, environmental and historical heritage of a region. The latter affect the quality of the tourist product as perceived by the tourists. Consequently, they also affect the tourist's subjective judgement of satisfaction based on the quality of the tourism experience they have 'consumed'. The present paper utilizes data drawn from an EU Research Project (SPRITE QLK5-CT-2000-01211) survey conducted in two regional sites of rural tourism in Greece. Analysis and results focus especially on comparisons between the two study regions. Further, policy implications as regards the development of the rural tourism product, are also discussed.
Keywords: 330